Effects of TiC Addition on Mechanical Behavior and Cutting Performance of Powder Extrusion Printed Cemented Carbides - Bisheng Zhong; Dezhi He; Xin Deng; Peishen Ni (Metals)
This study addresses the limited research on the mechanical behavior and cutting performance of additive manufactured cemented carbides with high TiC content, which has impeded the rapid development of additive manufacturing in carbide cutting tools. Using powder extrusion printing (PEP) additive manufacturing technology, we successfully fabricated WC-10TiC-12Co and WC-20TiC-12Co carbides with a relative density exceeding 97%. We investigated the effects of TiC content on the mechanical properties and cutting performance of WC-12Co carbide tools. The results show that TiC addition significantly affects the mechanical properties and cutting performance of PEP-processed carbides. Adding 10 wt.% and 20 wt.% TiC increases the Vickers hardness to 1403 HV30 and 1496 HV30, respectively, compared to 1317 HV30 for WC-12Co without TiC. However, TiC addition reduces the flexural strength from 2025 MPa for WC-12Co to 1434 MPa with 10 wt.% TiC and further to 915 MPa with 20 wt.% TiC. Tribological testing indicates that TiC addition reduces the friction coefficient and enhances wear resistance. HT250 cutting tests reveal that TiC addition significantly improves wear resistance and reduces workpiece surface roughness, particularly during longer cutting durations. This study broadens the scope of carbide materials suitable for PEP additive manufacturing.